PENGEMBANGAN MEDIA BOARD GAME MONOPOLI PADA MATA PELAJARAN INFORMATIKA MATERI SISTEM KOMPUTER KELAS X - Nabila Putri, Ahnaf; Augrah, Septriyan; Kurnia, Reni; Alfahani, Khairul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the use conventional media such as textbooks and presentation slides in Informatics learning at grade X of SMAS Adabiah 2 Padang, which have been unable to encourage active student engagement. A survey of 62 grade X students revealed that 71% preffered learning through educational games, while limited acces to the internet and further hindered optimal technology-based learning. This study aimed to develop a Monopoly board game learning medium on the Computer Systems topic in grade X Informatics that is valid, practical, and effective for use in the learning procces. The research employed as a Researche and Development (R&D) method using the ADDIE model, convering the stages of Analyze, Design, Development, Implementation, and Evaluation. The resulting product is a Monopoly board game equipped with individual and collaboration question card, asset card, a game board, and a playing guide, all aligned with the Learning Outcomes and Learning Objectives. Validity testing yielded score of 80% on the material aspect (Valid), and an average 94,7% on the media aspect (Very Valid). Practicality testing produced scores of 89% from teachers and 82,4% from student, both classified as Very Practical. Effectiveness testing using the N-gain score generated an average of 69,33%, categorized as Sufficiently Efective in improving student’s cognitive outcomes. These results indicate that the developed medium meets the criteria of valid, practical, and effective, making it suitable for use as a supporting learning medium for Informatics on the Computer Systems topic in grade X of senior high school.